POTENSI GUNUNG API LAMPUNG DAN PELUANG DAMPAKNYA - Anggraini, Welly; Octafiona, Era (Universitas Pendidikan Ganesha, 2024)
Lampung is one of the provinces in Indonesia which has quite high volcanic potential. This province has four active volcanoes, namely Mount Krakatau, Mount Anak Krakatau, Mount Sebesi, and Mount Rajabasa. These volcanoes have the potential to cause natural disasters, such as eruptions, earthquakes and tsunamis. This research aims to assess the potential of the Lampung volcano and its impact opportunities in terms of earthquake intensity and maximum ground acceleration. This research uses literature study and data analysis methods. The results of the research show that the intensity of earthquakes and maximum ground acceleration can influence the potential for natural disasters caused by volcanoes. High earthquake intensity can trigger volcanic eruptions, while high maximum ground acceleration can trigger tsunamis. This research provides recommendations for increasing community preparedness for natural disasters caused by volcanoes in Lampung. The government needs to socialize and educate the public about the potential dangers of volcanoes and ways to reduce disaster risks.